Android-based high school physical learning model - Mariati, Sari; Warti, Yani; Sari, Suci Nanda; Sari, Desi Purnama (Jurnal Patriot, 2024)
Problems: This research is based on the limited teaching and learning activities of physical education in schools, because the current pandemic situation still limits student learning activities in schools. Purpose: This research aims to produce a learning product for students as well as in the form of materials/textbooks and an android application that contains physical education materials to create more effective and efficient learning. Methods: The type of research method used in this study is research and development using the ADDIE Model. Results: This android-based PJOK learning model in the initial trial stage got a practicality percentage of 80% with the category "Practical". Then at the field trial stage, the percentage of practicality was 85% with the category "Very Practical". Conclusion: This shows that media products increase students' interest and motivation to learn